IDENTIFIKASI VARIABEL PENILAIAN PROPERTI PERUMAHAN BERDASARKAN PERSEPSI PENGHUNI PERUMAHAN - Fahirah, Fahirah (SMARTek, 2011)
Housing as one of the needs of the community continues to grow along with the economicimprovement of society. Completeness of facilities and infrastructure to support housingoperations and can be used as parameters for the realization of a standard residential andhabitable. So that the identification of variables related to the assessment of residential propertyneeds to be done to determine the variables that need to be considered by the partiesinvolved in property valuation.This study aims to identify the variables that greatly affect thevaluation of residential property based on the perceptions of residents of residential (consumer).Sources of primary data through questionnaires, interviews and surveys, and secondary datafrom the literature associated with research. The sampling system with random sampling of thepopulation with housing target is resident in South Palu. Data processed by descriptive statisticsand using the Likert scale for the percentage of residents perceptions of housing. The resultsshowed that the variables that greatly affect the valuation of residential property in South Palu:Pengawu, Bumi Anggur and Palupi Permai housing residents is based on the perception ofphysical variables and availability of housing facilities.